Enhancement of water barrier and antimicrobial properties of chitosan/gelatin films by hydrophobic deep eutectic solvent. (1st March 2023) - Wen, Haitao; Tang, Daobang; Lin, Yaosheng; Zou, Jinhao; Liu, Zhongyi; Zhou, Pengfei; Wang, Xuping
Abstract: Biodegradable chitosan/gelatin (CS/GEL) films have attracted attention as food packaging, but the poor water sensitivity and functional limitations of these films should be addressed. In this study, the hydrophobic deep eutectic solvent (DES, 0–15 %) consisting of thymol and octanoic acid was used to improve the water resistance and antibacterial performance of the CS/GEL composite films. FTIR and SEM analyses revealed a strong interaction between the CS/GEL matrix and DES. The films blended with DES showed increased water contact angle values and thermal stability. Furthermore, the addition of DES resulted in a significant increase in the elasticity and decrease water vapor transmission rate (WVTR). The CS/GEL films blended with 9% DES showed a 38.5% decrease in WVTR compared to those without DES. Additionally, the DES-containing film displayed good antibacterial activity against Staphylococcus aureus and Escherichia coli . Overall, the CS/GEL-DES composite films are expected to contribute an improvement to food packaging. Graphical abstract: Unlabelled Image